THE ROLE OF THE BANGKA BELITUNG NAVAL BASE IN SUPPORTING THE SEA SECURITY OPERATIONS IN THE INDONESIA ARCHIPELAGIC SEA LANE I - Manahan Budiarto Pandjaitan; Panji Suwarno; Gunardi Gunardi (Jurnal Pertahanan & Bela Negara, 2019)
The work areas that are the responsibility of the Bangka Belitung Naval base are still quite vulnerable and responsible for problems and difficulties that could disrupt the ALKI I or the Indonesian archipelagic sea lane I. The area for which the naval base of Bangka Belitung is responsible, is not balanced. However, it must continue to provide the best support for all KRI (Warships of the Republic of Indonesia) which anchored in the Bangka Belitung Naval Base. This study tries to analyze the role of the Bangka Belitung Naval base in supporting maritime security operations in ALKI I. The study uses descriptive qualitative methods about understanding the Bangka Belitung Naval base in supporting maritime security operations at ALKI I. This study uses the role of base theory, Sea Power theory and Navy trinity theory. The results of the study show that the Bangka Belitung Navy Base has not yet supported KRI or not to carry out the provision. Therefore, it is agreed that the Bangka Belitung Naval Base would provide complete facilities and infrastructure including anchoring, to be able to support KRI to operate safely at sea in assisting sovereignty in the ALKI I region.Keywords: Naval Base Role, Maritime Security, ALKI I